Assessing the performance of motorcyclists' impact protectors in simulated ATD knee and shoulder impacts. (17th February 2019) - Meredith, L.; Albanese, B.; Whyte, T.; Gibson, T.; Fitzharris, M.; Baldock, M.; Brown, J.
Abstract: Objective: Fractures are a common injury among motorcycle riders and can have serious health implications. Impact protection (IP) has been designed to help prevent fractures, yet there are conflicting opinions as to whether this IP does in fact help prevent fractures in real-world crashes. This work aimed to (1) use simulated dummy impacts to examine whether existing types of IP could reduce the force transferred to the underlying bone to below fracture tolerance levels and (2) investigate whether current European Standard (EN 1621-1) test procedures for impact protectors designed for motorcyclists are sufficient to ensure fracture protection. Method: Twenty-three shoulder and 7 knee IP specimens were tested using a 23-kg impactor contacting axially along the clavicle and femur of an anthropomorphic test device (ATD) at an energy level corresponding to the fracture tolerance of these bones. Sixteen IP specimens were the same as those worn by motorcycle riders involved in crashes where injury outcome was known (knee: n  = 3; shoulder: n  = 13) and the IP had been previously tested to EN 1621-1. Other IP tested represented a wide range of IP available for purchase at a motorcycle accessory store. Double and triple layers of IP were also tested. Energy attenuated during the dummy impacts was compared to energy attenuated when tested to EN 1621-1. Results: Of the 23 shoulder IP tested, the average percentage reduction of transferred force to the shoulder from the baseline test was 7.6 ± 4.8%. The percentage reduction of transferred force to the knee from the baseline was 43.9 ± 7.5%. The entire group of knee IP tested reduced the transferred force to the knee to below the 10-kN injury threshold for the femur. There was a positive but nonsignificant correlation between the ATD test and the EN 1621-1 impact test performance, suggesting that the European standard test method likely provides a good indication of IP performance. However, given the low correlation coefficient, the relationship between IP performance in the European standard test method and injury protection remains unclear. Conclusion: Though the energy attenuation test method in the European standard may be an appropriate approach, distinct differences in injury protection performance observed between knee and shoulder IP indicate that there may be a need for different performance criteria for IP designated to protect different body regions.